(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Technology has forced businesses to remain flexible, adapting their operations to newer and better technological advances. The purpose of this paper is to highlight the Impact of Information Technology (speed, accuracy, flexibility, consideration) on Accounting Information Quality of SFAC NO 8,2010 (relevance, faithful representation, comparability, verifiability, timeliness, understandability). By using the model that sheds light on the complex nature of interactions between variables (Information Technology and Accounting Information Quality) that can help the organization plans to adopt Information Technology system. The main data for an analysis are from the Survey of how technology has had a (positive – or negative) effect in accounting applications and whether information technology in accounting makes effect on the quality of financial reporting in Saudi Arabia which is a sample- based survey of Saudi Arabia automated banks. The author used the mean, standard deviation, regression models for the analysis of the underlying variables. The research showed that speed and flexibility are the most technological effects on accounting applications, and Relevance and Faithful Representation in Fundamental characteristics affected by using technology, respectively. which is the same as 2010 FASB development. and the enhanced characteristics that consist of Comparability, Understandability, Timeliness, and Verifiability are respectively affected by using technology which is not the same as 2010 FASB characteristics arrangement,